2020
DOI: 10.47838/acem.26011977.11162020.asmeda.3.0
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Honey Administration on Petrol-Induced Oxidative Stress and Hepatotoxicity in Sprague-Dawley Male Rats

Abstract: Background: Exposure to petrol is common among individuals working in oil refineries, oil fields, filling stations, automobile mechanical workshops. Exposure to petrol is associated with a number of health hazards including hepatotoxicity and oxidative stress. Honey is rich in many antioxidants such as catalase, flavonoids, thiamine, riboflavin, pyridoxine, pantothenic acid, ascorbic acid and nicotinic acid and was recently reported to reduce petrol-induced hepatotoxicity and nephrotoxicity. Materials and Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…On the other hand, the use of this plant has also proved its effectiveness against heavy metal poisoning. It was reported that curcumin attenuates lead-induced cerebellar toxicity in rats via chelating activity and inhibition of oxidative stress [9]. Despite the potential proven effect of C. longa against the toxic effect of Al on the male reproductive system, few or no studies have investigated its effect on the prostatic gland.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the use of this plant has also proved its effectiveness against heavy metal poisoning. It was reported that curcumin attenuates lead-induced cerebellar toxicity in rats via chelating activity and inhibition of oxidative stress [9]. Despite the potential proven effect of C. longa against the toxic effect of Al on the male reproductive system, few or no studies have investigated its effect on the prostatic gland.…”
mentioning
confidence: 99%
“…Tissue biochemical analysis involved measuring malondialde-hyde (MDA), catalase (CAT), and superoxide dismutase (SOD) concentrations [10]. Hormonal analysis was performed on serum samples to determine testosterone levels using radioimmunoassay methods with commercial kits (VIDAS Assays, BIOMERIEUX) [9]. Histological studies included hematoxylin-eosin staining [11], and toluidine blue staining to assess apoptosis and inflammation levels [12].…”
mentioning
confidence: 99%